DEVELOPMENT OF A MULTIPLE-CHOICE TEST INSTRUMENT FOR CLUTCH SYSTEM LEARNING - Moh Zainul Muttaqin; Ranu Iskandar (JURNAL EDUSCIENCE, 2026)
Purpose – This research aims to develop a daily test instrument for clutch system material that is valid, reliable, and has good question item characteristics for students of the Automotive Engineering Education Study Program, Universitas Negeri Semarang.Methodology – The research method used is R&D with the ADDIE model. The test subjects in this study comprised 38 students selected through purposive sampling. Data were collected through a feasibility validation sheet completed by an expert validator and the results of student responses from the instrument trial, consisting of 10 multiple-choice questions. The analysis of empirical data included validity and reliability tests, level of difficulty, discriminative power, and distractor effectiveness.Findings – The results of the analysis showed that all 10 questions were declared empirically valid with values ranging from 0.594 to 0.877 (r_table = 0.329). The reliability coefficient of the instrument was obtained as (r_11) = 0.912 (very high category). The characteristics of the question items showed the proportion of the ideal difficulty level (50% easy, 40% medium, and 10% difficult), the effectiveness of the deceitful function was 83.33% (25 out of 30 deceitful), and the discriminating power was categorized as sufficient to very good (3 adequate, 4 good, and 3 very good).Contribution – This study contributes to the development of a daily test instrument for clutch system material that has been proven to be valid, reliable, and to have good item quality for students of the Automotive Engineering Education Study Program, Universitas Negeri Semarang. The developed instrument can be used as an objective learning evaluation tool.